Akurasi Makna Dalam Kamus Bahasa Arab Digital - Muh. Kadri (Pascasarjana Universitas Islam Negeri Mataram, 2024)
This research aims to analyze the accuracy of meaning in Arabic dictionaries by comparing digital dictionaries and printed dictionaries. The method used is qualitative analysis of selected word definitions from both types of dictionaries, obtained from journal sources and articles published between 2020 and the present. The results of the analysis show that printed dictionaries have a higher level of congruence in meaning and more complete definitions, often accompanied by examples of usage in sentences that help contextual understanding. On the other hand, digital dictionaries tend to provide shorter and less in-depth definitions. Although digital dictionaries offer ease of access and faster updates, they still face challenges in providing contextual and accurate definitions. The recommendation for users is to utilize both types of dictionaries as complementary tools, with digital dictionaries for quick searches and print dictionaries for deeper and more accurate understanding, especially in academic and professional contexts.